The development of VisLT visualization service in Openstack cloud infrastructure. (January 2017) - Pacevič, R.; Kačeniauskas, A.
Highlights: VisLT visualization service is developed in the OpenStack cloud infrastructure. The partial dataset transfer from the object storage is developed as the middleware. The partial dataset transfer took from 1.7% to 6.7% of the full dataset transfer. Virtualized GPU rendering and monitoring is implemented on Xen HVM. The performance difference between the native hardware and the VM is equal to 5.6%. Abstract: The paper presents the development of visualization software as a service in the OpenStack cloud infrastructure. VisLT cloud visualization service is developed for visualizing the results computed and stored in the private cloud infrastructure. Partial dataset transfer from the OpenStack object storage is developed to reduce the communication between different parts of the cloud infrastructure. The cloud services are developed by using Apache jclouds API to enhance the management of cloud infrastructure and to increase the accessibility of the visualization service. GPU is virtualized as a PCI device employing direct pass-through technology on the hardware virtual machines of Xen hypervisor to ensure fast remote rendering, which is a key feature of distributed visualization systems. The extraction of crack surfaces and computations of flows through the aortic valve are considered as pilot applications of the developed visualization service. The performance of VisLT measured on the XEN hardware virtual machines is compared to the performance attained on the native hardware.